The power of knowledge about dementia in Latin America across health professionals working on aging - Ibañez, Agustin Mariano (2021)
Introduction: Expert knowledge is critical to fight dementia in inequitable regions like Latin American and Caribbean countries (LACs). However, the opinions of aging experts on public policies’ accessibility and transmission, stigma, diagnostic manuals, data-sharing platforms, and use of behavioral insights (BIs) are not well known. Methods: We investigated opinions among health professionals working on aging in LACs (N = 3365) with regression models including expertise-related information (public policies, BI), individual differences (work, age, academic degree), and location. Results: Experts specified low public policy knowledge (X2 = 41.27, P <.001), high levels of stigma (X2 = 2636.37, P <.001), almost absent BI knowledge (X2 = 56.58, P <.001), and needs for regional diagnostic manuals (X2 = 2893.63, df = 3, P <.001) and data-sharing platforms (X2 = 1267.5, df = 3, P <.001). Lack of dementia knowledge was modulated by different factors. An implemented BI-based treatment for a proposed prevention program improved perception across experts. Discussion: Our findings help to prioritize future potential actions of governmental agencies and non-governmental organizations (NGOs) to improve LACs’ dementia knowledge.